The use of calcium hydroxyapatite in aesthetic medicine – properties, mechanism of action, and clinical safety - Zimnoch, Barbara; Chmura, Katarzyna; Rendaszka, Katarzyna; Kowalska, Katarzyna; Pyziołek, Marta; Bonarska, Marta; Kwaśniewska, Paulina; Stróżna, Małgorzata; Najbar, Joanna Monika (Quality in Sport, 2025)
Background: Aesthetic medicine has advanced rapidly, with dermal fillers becoming essential for facial rejuvenation and contouring. Among biostimulatory fillers, calcium hydroxylapatite (CaHA) is widely studied for its volumizing effect, regenerative potential, and long-lasting results. Aim: This paper reviews CaHA in aesthetic medicine, covering its properties, biodegradability, biocompatibility, mechanism of action, clinical applications, injection techniques, and safety. Methods: Clinical studies, histologic analyses, in vitro research, and systematic reviews were examined to assess CaHA’s effects on tissue remodeling, collagen production, and treatment outcomes. Results: CaHA consists of microspheres in a carboxymethylcellulose gel, providing immediate volume and stimulating neocollagenesis. Studies show increased type I and III collagen, fibroblast activity, and extracellular matrix improvements. Clinically, it effectively treats nasolabial folds, marionette lines, midface volume loss, neck and décolleté laxity, hand rejuvenation, and certain scars. Diluted forms are useful in thin skin areas. Adverse reactions are mostly mild and temporary; serious events are rare and usually technique-related. Conclusions: CaHA is a versatile biostimulatory filler offering immediate support and long-term tissue regeneration. It enhances collagen, improves skin quality, and delivers predictable, safe outcomes for facial and extrafacial rejuvenation.